The Influence of Resource and Organization Based Views and Organization Strategy on Real Estate Business Performance: A Case study of Condominium Business in Bangkok - Chimpalee, Athicha (KASEM BUNDIT JOURNAL, 2019)
The main purpose of this research was to study the influence of resource based views, institutional based views, and organization strategy on the one hand on business performance on the other. The data were collected from the sample of 500 persons in real estate business public companies and in-depth interview of 6 chief executive officers. The structural equation model (SEM) was the main statistical method used to examine the validity of the causal relation. The findings showed that the adjusted SEM of the influence of resource based views, institutional based views and organization strategy on firm performance was consistent with empirical data.